2020
DOI: 10.3390/plants9050625
|View full text |Cite
|
Sign up to set email alerts
|

Distribution Pattern of Gymnosperms’ Richness in Nepal: Effect of Environmental Constrains along Elevational Gradients

Abstract: Understanding the pattern of species distribution and the underlying mechanism is essential for conservation planning. Several climatic variables determine the species diversity, and the dependency of species on climate motivates ecologists and bio-geographers to explain the richness patterns along with elevation and environmental correlates. We used interpolated elevational distribution data to examine the relative importance of climatic variables in determining the species richness pattern of 26 species of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(33 citation statements)
references
References 58 publications
14
19
0
Order By: Relevance
“…A negative relationship between species richness and climatic seasonality has previously been reported (Gao & Liu, 2018;Kristiansen et al, 2011;Liu et al, 2017;Panda et al, 2017;Pandey et al, 2020;Shrestha et al, 2017), and our study supports the climate seasonality hypothesis. The MAT in China is between -25 and 25°C,…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…A negative relationship between species richness and climatic seasonality has previously been reported (Gao & Liu, 2018;Kristiansen et al, 2011;Liu et al, 2017;Panda et al, 2017;Pandey et al, 2020;Shrestha et al, 2017), and our study supports the climate seasonality hypothesis. The MAT in China is between -25 and 25°C,…”
Section: Discussionsupporting
confidence: 91%
“…Thus, multiple modeling approaches could be most suitable for quantifying the contributions of various hypotheses toward spatial richness patterns. Moreover, there are studies that explain the species richness patterns of gymnosperms along environmental gradients in the Himalayas (Pandey et al, 2020;Subedi, Bhattarai, Perez, & Sah, 2019). Tian (2002), Ying, Chen, and Zhang (2004), Li, Shen, Ying, and Fang (2009), Jiang, Cheng, and Yin (2010), and Yang (2015) have also studied the distribution of gymnosperms in China, while the mechanism that determines richness patterns were not considered.…”
Section: Introductionmentioning
confidence: 99%
“…Temperature and water availability have a direct relationship with the pattern of species richness by accelerating the metabolic activities in plants (Pausas and Austin, 2001;Currie et al, 2004). Water availability and temperature have a different response to the species diversity; however, their combined effect determines the synergic mechanisms of plant species richness (Vetaas and Grytnes, 2002;Gao and Liu, 2018;Pandey et al, 2020b). Previous studies showed the positive quadratic (mid-elevation peak) relationship between species diversity and temperature and water availability along elevation gradients (Bhattarai and Vetaas, 2003;Kluge et al, 2017;Subedi et al, 2019;Pandey et al, 2020b).…”
Section: Introductionmentioning
confidence: 99%
“…Available studies suggested different patterns of EDG that can be summarized into four patterns of species richness-(i) decrease in species with increasing elevation, (ii) increase in species with increasing elevation, (iii) highest number of species at mid-elevation, forming a unimodal pattern, and (iv) less number of species at mid-elevation, creating a "U"-shaped pattern. Most researches have explained a significant role of EDG in defining the diversity patterns of plants (Rahbek, 1995;Lomolino, 2001;Bhattarai and Vetaas, 2003;Bhattarai et al, 2004;Wang et al, 2007;Gao et al, 2017;Kluge et al, 2017;Gao and Liu, 2018;Subedi et al, 2019;Pandey et al, 2020b). Lomolino (2001) reviewed and summarized the studies linking the elevational distribution of species richness, and identified the further need for comparing the richness patterns and the factors that determine EDG.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation